Implementation analysis of vacuum area gripping system in pick and place machinery in wooden door company - Edilla; Julfrianto Julfrianto (JTTM : Jurnal Terapan Teknik Mesin, 2023)
Companies must grow in order to boost efficiency and production quality due to competition in the wood industry, particularly in the production of increasingly hard wooden doors. The issue that businesses face frequently is the occurrence of product flaws during the manufacture of wooden doors. A method for lifting, positioning, and moving door goods has been created by PT XYZ, one of the export-quality wooden door firms. By reducing product flaws, this study hopes to raise the quality of wooden doors. The pick and place machine's grasping system is the primary cause of the high prevalence of impairment. There are specific flaws in the door-gripping mechanism that increase the likelihood of product failures from falling and workplace accidents. After reworking the vacuum area gripping system, which uses suction technology, one of the Schmalz brands manufactured in Germany is outfitted with an external suction motor as a source of suction energy. The tool can lift loads up to 50 kg in accordance with specifications at a consistent speed, according to development results